Responsiveness of the EAT-10 to Clinical Change in Head and Neck Cancer Patients with Dysphagia. (2nd January 2020) - Sinn, F. S.; Charters, E.; Stone, D.; Janabi, M.; Bogaardt, H.
Abstract: Purpose: This retrospective study evaluated the external responsiveness of the Eating Assessment Tool-10 (EAT-10) to clinical changes in a single cohort ( n = 105) treated with chemoradiotherapy (CRT) or radiotherapy (RT) for head-and-neck cancer. Method: Patients completed the EAT-10 four times: (I) Within two weeks of commencing (C)RT, (II) in the final week of (C)RT, (III) two weeks post-(C)RT and (IV) following discharge from speech-language pathology services. Data was compared to their oral intake status, using the Functional Oral Intake Scale (FOIS). Result: Using Cohen's d, changes in the EAT-10 and FOIS were comparable, however, a difference was observed at data-point IV. At data-points I, II and III, the EAT-10 had a strong negative correlation with the FOIS (Spearman's ρ= −0.81, −0.80 and −0.81 resp.). At data-point IV the correlation strength decreased (Spearman's ρ= −0.69). Fisher's Z transformation found no statistically significant correlation coefficient differences between data-points I, II and III. A significant difference in correlation was found between these data-points and data-point IV ( p = 0.027; p = 0.039 and p = 0.022 resp.). A very high internal consistency was found (Cronbach's α > 0.95) for all data-points. Conclusion: This study's results indicate that the EAT-10 has weaknesses in the external responsiveness and has redundancy of its question items.